PENGELOLAAN DESA WISATA BELIMBING MENUJU PARIWISATA BERKELANJUTAN KECAMATAN PUPUAN, KABUPATEN TABANAN, BALI - Digna Merian Andriani; I Nyoman Sunarta (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2015)
Abstract As one of the tourism village in Bali, Belimbing Village has offered the traditional culture of people and nature environmental which are as the tourist attractions. This study discusses the management of the Belimbing Tourism Village which was managed by the Perbekel Belimbing Village with various staff in it and also formed Pokdarwis (Kelompok Sadar Wisata), under the auspices of the Government of Tabanan. Management of Belimbing Tourism Village is the independent management of the entire staff is indigenous people, also in cooperation with the private sector, but only in terms of improving the human resources quality. The management has a positive impact both for society and for the development tourism village. Sustainable tourism is a challenge in the management of a tourist village to create a balance or harmony between ecology, economy and social culture. This study is expected to be useful in providing advice and solutions to problems faced in the management of Belimbing Tourism Village towards sustainable tourism, with a qualitative descriptive method. There is a description of Belimbing Tourism Village management include six aspects such as organizational, financial, marketing, production and operations, human resources, and aspects of management information systems. It shows that the manager has sought to facilitate and provide a maximum of various aspects required for tourists. But a lot of things that still need to be addressed, including addressing management problems faced in order to optimally towards sustainable tourism.